Infants' Age and Walking Experience Shapes Perception-Action Coupling When Crossing Obstacles - Vieira, Ana P. B.; Carvalho, Raquel P.; Barela, Ana M. F.; Barela, Jose A. [UNESP] (Sage Publications Inc, 2019)
This study examined the effects of age and walking experience on infants' ability to step over an obstacle. We videotaped 30 infants with one (mean [M] age = 12.6 months), three (M age = 14.7 months), and six months (M age = 17.7 months) of walking experience walking on a pathway with and without an obstacle. We found a shorter stride and slower velocity for infants with one month of walking experience and for the walking condition with an obstacle than for other experience groups or for walking without an obstacle. Across all groups, the horizontal distance between an infant's foot and the obstacle was larger for the trailing leg than for the leading leg. The vertical distance for both legs was similar among 1-month walkers, increased for 3-month walkers, and was similar for the trailing leg of the 6-month walker group. The percentage of the interlimb coordination relative phase for the leading limb was smaller for 3- and 6-month walker groups. In conclusion, age and walking experience contribute to improving coupling between sensory information and motor action and to organization for stepping over an obstacle in infants.
Keywords: locomotion; infants; perception-action; experience; obstacle